The Influence of NPF, CAR, and FDR on Financing Murabahah-Based with Third Party Fund as Moderator in Sharia Commercial Banks 2015 – 2022 - Setiawan, Deny; Febriansyah, Muhammad; Ardian, Ardian (IKONOMIKA, 2022)
This study aims to analyse the influence of Non-Performing Financing (NPF), Capital Adequacy Ratio (CAR), and Financing Deposit Ratio (FDR) on Financing Murabahah-Based with Third-Party Fund as a Moderator 2015 – 2022. This study uses three variables that encompass independent variable, dependent variable, and moderation variable. Independent variables consist of Non-Performing Financing (NPF), Capital Adequacy Ratio (CAR), and Financing Deposit Ratio (FDR), dependent variable consists of Financing Murabahah-Based, and moderation variable consists of Third-Party Fund that will subsequently be analysed with Moderated Regression Analysis (MRA) by comparing the R-square Value before and after the tally include and exclude the moderation variable in the statistical measurement. The data used in this study were monthly data from January 2015 until January 2022. The research method that was used in this study was descriptive quantitative analyse by using linear regression analysis through path analysis which was processed by using E-Views 10. The results of this study show that Non-Performing Financing (NPF) and Financing Deposit Ratio (FDR) influence negatively and significantly Financing Murabahah-Based, Capital Adequacy Ratio (CAR) influences positively and significantly on Financing Murabahah-Based, and Third-Party Fund moderates the relationship between Non-Performing Financing (NPF) and Financing Murabahah-Based, Capital Adequacy Ratio (CAR) and Financing Murabahah-Based, and Financing Deposit Ratio (FDR) and Financing Murabahah-Based.